THE ANALYSIS OF SOFT SKILL FOR EMPLOYEE PERFORMANCE IN BANKING INDUSTRY - Kumendong, Andreano .; Pangemanan, Sifrid S.; Pandowo, Merinda . (Universitas Sam Ratulangi, 2018)
Â Abstract : Company and employee are two diffrent element that cannot be seperated. With low perforamance or dissatisffy employee can make decreasing profit for company. on the other hand, smart and good performance will make great company. with great company thier will be more advantage than other company.one strategies increase performance by employee is to know how to use skill in certain situation. They have have soft skill to be improve. The objective of this research is to analysis of applying soft skill for employee performance in bank industry. The research method base on qualitative approach and meansurement skill will be :.communication, problem solving, team working, an ability to improve learning and performance, motivation, judgement, leadership, and initiative. The result is based on this research is most of employee applying soft skill for their work environment. The recommendation is soft skill is very important and cannot be separated with work, so in order to be more competitive soft skill must always be upgradeÂ Keyword : analysis of soft skill, performance, employee, banking industryÂ